PENGARUH , INTELEGENCE QUOTIENT, EMOTIONAL QUOTIENT DAN SPIRITUAL QUOTIENT TERHADAP KINERJA KARYAWAN STUDI PADA PT. BUMI MENARA INTERNUSA - Roni Roni; Hadi Sunaryo; Pardiman Pardiman (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACT The purpose of this study is to describe the intelligence quotient, emotional quotient, spiritual quotient, and employee performance and to determine the effect of intelligence quotient, emotional quotient, and spiritual quotient on employee performance partially and simultaneously. This research method uses quantitative methods and this type of research is explanatory research. The sample of this study was 47 employees of PT. Bumi Menara Internusa. To obtain accurate and detailed data, this study uses a data collection method with a questionnaire. Analysis of the data used is the instrument test, normality test, multiple linear regression analysis, classic assumptions, and hypothesis testing using SPSS 18 for Windows. The results of this study indicate that intelligence quotient, emotional quotient, and spiritual quotient simultaneously affect the performance of employees of PT. Bumi Menara Internusa. While partially, intelligence quotient influences employee performance, emotional quotient influences employee performance, and spiritual quotient affects employee performance of PT. Bumi Menara Internusa.Keywords: Intelligence Quotient, Emotional Quotient, Spiritual Quotient and Employee Performance.